Implementation of Web Engineering in the Design and Development of the Website Portal for SMA Negeri 1 Martapura - Bhagaskara, Dewa Nihan; Udariansyah, Devi (International Journal Software Engineering and Computer Science (IJSECS), 2024)
This research aims to improve the quality of educational services at SMA Negeri 1 Martapura by developing a website portal that is more attractive and user-friendly. Even though SMA Negeri 1 Martapura has an accessible website, there are shortcomings in the interface and menu structure that are less attractive to users. To overcome these challenges, this research focuses on developing a new website portal using the PHP programming language and MySQL as a database. The resulting website portal is designed to improve user interaction with a more intuitive interface and more comprehensive features. By involving 53 permanent teachers (PNS/P3K), ten non-permanent teachers, and 953 active students, the development of the SMA Negeri 1 Martapura website portal aims to provide better services to the entire school community. With an attractive and easy-to-use website portal, it is hoped that it will improve the user experience in accessing information about schedules, activities, and various other educational services offered by SMA Negeri 1 Martapura. Overall, this research aims to positively contribute to increasing the effectiveness and efficiency of academic services at SMA Negeri 1 Martapura through sophisticated and user-friendly information technology.